Knowledge Management Strategies for Enhancing the Business Potential of Coffee Shops in Mueang Chiang Mai District Chiang Mai Province - Karahong, Pisittakorn; Angasinha, Chatwarun (Journal of Dhamma for Life, 2026)
This study aimed to 1) examine knowledge management practices in coffee shop businesses in Chiang Mai Province, 2) analyze opportunities, problems, and obstacles faced by coffee shop entrepreneurs, and 3) propose knowledge management guidelines to enhance the capacity and sustainability of coffee shop businesses in Mueang Chiang Mai District, Chiang Mai Province. A qualitative research design was employed, combining documentary research with field data collection. In-depth interviews were conducted with 13 key informants selected through purposive sampling, consisting of coffee farmers, baristas, coffee shop owners, and coffee consumers. The research instruments included a semi-structured in-depth interview guide and field note documentation. Data were analyzed using content analysis and interpretive thematic synthesis. The findings revealed that although coffee shop businesses in Chiang Mai have experienced continuous growth and high diversity, most entrepreneurs still lack a systematic knowledge management framework. Key deficiencies were identified in cost management, human resource management, marketing, and risk management. Much of the existing knowledge remains tacit, relying heavily on individual experience rather than structured organizational systems. This situation makes businesses vulnerable to economic fluctuations and external crises. The application of knowledge management concepts can facilitate the systematic collection, sharing, and development of organizational knowledge, thereby improving decision-making efficiency and enhancing competitive advantage. This study proposes an integrated knowledge management approach that links people, processes, and collaborative learning within coffee shop enterprises. Such an approach is expected to strengthen business resilience, reduce operational risks, and support sustainable development within the context of Chiang Mai as a cultural and tourism-oriented city.